Examining Sex-Based Measurement Invariance in the Youth Level of Service/Case Management Inventory - Kitzmiller, Mary (Crime & delinquency, 2023)
Juvenile risk assessments are used to predict likelihood of reoffending in court-involved youths, and inform several decisions throughout court supervision. Accordingly, it is critical that the psychometric properties of juvenile risk assessment instruments are consistent for youths across demographic subgroups, particularly biological sex. This study tests the measurement invariance of the Youth Level of Service/Case Management Inventory (YLS/CMI) by sex. Analyses draw from 2,384 youths who were adjudicated as delinquent in a county-level juvenile court. Results indicate that the factor configuration and structure of the YLS/CMI are consistent for youths across sex. However, boys and girls differ appreciably in risk profile. Findings validate the use of the YLS/CMI and highlight the importance of responsivity to sex-based variation in criminogenic risk.